2021
DOI: 10.3389/fpsyt.2021.714209
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Music Therapy on Perceived Pain, Mental Health, Vital Signs, and Medication Usage of Burn Patients Hospitalized in the Intensive Care Unit: A Randomized Controlled Feasibility Study Protocol

Abstract: Background: Burn patients experience major physiological and psychological stressors during treatment and rehabilitation, including elevated levels of pain, anxiety, stress, or depression. Music interventions inclusive of music therapy (MT) have been shown to improve such symptoms, but rigorous clinical trials investigating specific music therapy methods in adult burn patients are scarce.Methods: This is a single center Randomized Controlled Trial (RCT) protocol with two parallel arms. Participants are 81 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…"Therapeutic music listening should not be confused with music therapy". The first form of music used in the form of music therapy can only be conducted by a certified music therapist, while therapeutic music listening is conducted by nurses, among others, through patients listening to music on headphones or volunteers playing live music [21]. Golino et al, 2019, in their publication, present a juxtaposition of the terms music therapy and music listening [3].…”
Section: Types Of Music Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…"Therapeutic music listening should not be confused with music therapy". The first form of music used in the form of music therapy can only be conducted by a certified music therapist, while therapeutic music listening is conducted by nurses, among others, through patients listening to music on headphones or volunteers playing live music [21]. Golino et al, 2019, in their publication, present a juxtaposition of the terms music therapy and music listening [3].…”
Section: Types Of Music Therapiesmentioning
confidence: 99%
“…The authors also found that playing music to patients from a player is far less expensive than using individual headsets for each patient [29,33]. [21,23,24], as well as reduce sleep disturbances [21,25] and have a relaxing effect and regulate breathing [22]. Studies by Dallı et al, Browning et al, and Jawaharani et al emphasize that music therapy reduces the incidence of delirium [25,29,30], and Yekefallah et al pointed out that it can improve cognitive function [32]; in addition, it can result in reduced costs of drug treatment [26].…”
Section: Types Of Music Therapiesmentioning
confidence: 99%
“…Areas of study in music therapy for pain in adults occur most frequently in palliative care and in debridement [ 33 , 34 , 35 ]. Surprisingly, it is common for studies to leave out patient culture in the assessment of how to treat pain.…”
Section: Assessment-integrative Mechanismsmentioning
confidence: 99%
“…Approaches permitting treatment individualization within a standard protocol are perhaps highest in the medical EBP hierarchy. Few such studies involve music therapy targeting pain in individuals, though these do not report outcomes on pain measures ( 19 , 20 ) or the results are not yet published ( 21 ). Examples in other contexts include clinical improvisation for depression ( 22 , 23 ) and autism ( 24 ) and customized songs for pre-term infants and their caregivers ( 25 ).…”
Section: Research Approachesmentioning
confidence: 99%